Improved image quality and reduced acquisition time in prostate T2-weighted spin-echo MRI using a modified PI-RADS-adherent sequence - Stephen J. Riederer; Eric A. Borisch; Adam T. Froemming; Roger C. Grimm; Sara Hassanzadeh; Akira Kawashima; Naoki Takahashi; John Thomas (European Radiology Experimental)
Abstract Background Prostate imaging reporting and data system (PI-RADS) v2.1 guidelines for magnetic resonance imaging acquisition define a standard of 0.40 mm × 0.70 mm in-plane resolution (0.280 mm2 pixel area), but adherence has been challenging. We questioned if a modification of a PI-RADS-adherent T2-weighted (T2WI) sequence to one having equivalent pixel area could allow reduced acquisition time but provide improved diagnostic quality (DQ). Methods An adherent T2WI sequence was modified by reducing the frequency sampling, thereby reducing the signal bandwidth (BW). This was compensated by increasing the phase sampling for an equivalent pixel area (0.50 mm × 0.57 mm = 0.285 mm2). The BW reduction allowed a two-fold reduction in averaging, also enabling reduced acquisition time. The adherent and modified sequences were evaluated in phantoms and 62 consecutive prostate MRI subjects. Images were evaluated individually by four radiologists using a four-point DQ scale and using prostate imaging quality (PI-QUAL)v2. Each reviewer also indicated any sequence preference. The Wilcoxon test was used. Results In the phantom, mean signal-to-noise ratios were equivalent for the two sequences; superior frequency resolution for the adherent sequence, and superior phase resolution for the modified sequence were shown. Across 62 participants, the median acquisition time was reduced by 23%, from 3:55 min:s to 3:01 min:s. For all three means of comparison (DQ, PI-QUALv2, reader preference), the modified sequence was significantly superior (p ≤ 0.037). Conclusion Modification of the PI-RADS standard (0.40-mm frequency resolution) to an equivalent, more isotropic pixel area (0.28 mm2) reduced acquisition time and improved image quality. Relevance statement Generalization of the PI-RADSv.2.1 minimum technical standard for T2WI in-plane resolution to be more isotropic preserves the targeted high resolution, allowing reduced acquisition time, also reducing motion sensitivity, and improving image quality. This approach may also reduce the need for rescanning poor-quality sequences. Key Points PI-RADSv2.1 suggests a standard T2WI sequence with 0.40 × 0.70 mm2 in-plane resolution. A modified PI-RADSv.2.1-adherent T2WI sequence with equivalent but more isotropic pixel area (0.50 × 0.57 mm2) allowed reduced scan times by 23% and significantly improved DQ. Superiority of the modified sequence appears due to reduced motion sensitivity. Graphical Abstract